CORRELATION BETWEEN INDEPENDENCE IN LEARNING AND MATHEMATICS LEARNING OUTCOMES TO FIFTH GRADE STUDENTS OF PUBLIC ELEMENTARY SCHOOLS IN GRABAG SUB-DISTRICT IN ACADEMIC YEAR OF 2019/2020 - Asworowati, Meirika Tri; Joharman, Joharman; Ngatman, Ngatman (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2020)
The study aimed to prove positive correlation between independence in learning and mathematics learning outcomes and to determine the contribution of independence in learning to mathematics learning outcomes for fifth grade students of public elementary schools in Grabag sub-district in academic year of 2019/2020. It was a quantitative research with correlation method. Sampling method was cluster random sampling with Statistical Product and Service Solution (SPSS) version 25. The data collection techniques were questionnaire to obtain independence in learning variable and test to obtain mathematics learning outcomes. Data analysis used pearson product moment correlation test with a significance level of 0.05 and used adjusted R square. The results showed that the value of correlation between students' independence in learning and mathematics learning outcomes was 0.339 with p-value = 0,000 (Sig. 0.000 <0.05). The value of adjusted R square was 11,5%. It concludes that there is positive and significant correlation between independence in learning to mathematics learning outcomes for fifth grade students of public elementary schools in Grabag sub-district.